Fabrication of emulsion-templated macroporous poly(ε-caprolactone) towards highly effective and sustainable oil/water separation. (9th September 2020) - Yang, Xiaocang; Yin, Zhengqiao; Zhang, Xiaoyu; Zhu, Yun; Zhang, Shengmiao
Abstract: A facile synthetic chemical strategy was descripted to produce porous poly(ϵ-caprolactone) (PCL) towards to a highly selective, reusable and degradable oil absorbent. The porous PCL was synthesized by organocatalyzed ring-opening polymerization (ROP) of ϵ-caprolactone (CL) in a tetradecane-in-CL high internal phase emulsion (HIPE). In this method, methanesulfonic acid (MSA) was used as an organocatalyst, and the block copolymer pluronic F127 acted as both emulsifier of the emulsion and initiator for the ROP of CL at a mild condition (37 °C). The molecular structure of copolymers could be tailored by changing the emulsifier concentration. The resulting polymers exhibited a controllable open-cell macroporous structure with HIPE as templates, and could be completely degraded. Absorption experiments showed the porous polymers absorbed gasoline, diesel, olive oil, or tetradecane from the water-oil mixture within 30 s, and the oils could be recovered simply by a centrifugation process at 3000 rpm. The absorbent had a full preservation of both the porous morphology and the absorption capacity in the performed six absorption/desorption cycles. These materials proved effective as oil absorbents for oil/water separation with not only a noticeable selectivity and recyclability performance, but also unprecedented safe disposability thanks to its degradability. Graphical abstract: Image 1 Highlights: A facile synthetic chemical strategy is descripted to produce poly(ɛ-caprolactone) (PCL) based oil absorbent. A block copolymer pluronic F127 acts as both emulsifier of the emulsion and initiator for the ROP of CL. The polymers have a controllable open-cell macroporous structure and a tunable molecular structure. The polymers absorb oils from water-oil mixture within 30 s, and the oils are recovered simply by centrifugation.